Implementation of IoT-Based Smart Parking with Automated Barrier and QR Code Validation - Asri Samsiar Ilmananda; Joshua Aldora Lian Djuk; Amadea Permana Sanusi (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2026)
The rapid growth of vehicles in urban areas has created significant challenges in parking management, particularly regarding operational efficiency and user experience. This research develops a smart parking system leveraging Internet of Things (IoT) technology, equipped with real-time monitoring capabilities, online reservation features, and automated validation using QR codes for four-wheeled vehicles. The hardware implementation utilizes ESP8266 NodeMCU as the main controller, infrared sensors for vehicle detection, and SG90 servo motors for automated gate operation. On the software side, a web-based application was developed using PHP and Node.js, serving as both user interface and control panel for parking operators. Testing results indicate that infrared sensors perform optimally within a 5-20 cm range, achieving response times between 100-153 ms. The QR code validation mechanism successfully identifies valid, expired, and unauthorized tickets with 100% accuracy under normal operating conditions. Servo motors demonstrate consistent performance with operation times ranging from 2.2-2.7 seconds for opening and closing the gate. Data synchronization between ESP8266 and the server achieves average response times of 120-135 ms on stable connections, complemented by automatic recovery capabilities following network disruptions. The implementation of this system proves effective in enhancing parking operational efficiency through validation automation, real-time monitoring, and reduction of human errors, positioning it as a viable smart parking solution within the smart city ecosystem.